Assessing Media Access and Use Among Latina Adolescents to Inform Development of a Physical Activity Promotion Intervention Incorporating Text Messaging. Issue 4 (July 2014) - Mojica, Cynthia M.; Parra-Medina, Deborah; Yin, Zenong; Akopian, David; Esparza, Laura A.
Increasing physical activity (PA) during preadolescence and adolescence is critical to reversing the obesity epidemic. A recent report described the promising role of eHealth—the use of new media for purposes of health promotion—in reducing and preventing childhood obesity. This study assessed access/use of various media (cell phones, computers, gaming systems, Internet) among adolescent Latino girls and examined the relationship between PA and media access/use. A convenience sample of 110 Latino girls ages 11 to 14 was recruited from Girl Scouts of Southwest Texas and other groups. The media survey was self-administered (April-July 2010) on personal digital assistants. Of the girls, 55% reported owning a cell phone and spending 40 (SD = 4.2) hours per week talking, texting, listening to music, and browsing the Internet. Cell phone access increased significantly with age (p = .029). Compared to those with no cell phone, girls with a cell phone have greater odds of reporting more than 5 days of PA in the past week (odds ratio = 5.5, 95% confidence interval [CI] = 2.1, 14) and engaging in daily physical education classes (odds ratio = 2.6, 95% CI = 1.1, 5.9). Since girls with cell phones report greater PA, cell phones may be an effective strategy for communicating with girls about engaging in PA.